The Artist's guide a practical guide to all aspects of painting & drawing - Wilkinson, John (Dorling Kinderley, 1998)
Written for amateur artists and beginners, this book demonstrates in word and images how easy it is to develop and enjoy art skills. "How to see" is the first, most important step of all, and the author explains how to discard instinctive preconceptions and learn to look all over again. Lighting, tone, composition, texture and perspective are among the themes explored, each approached with the aim of capturing a 3D view on a 2D surface. Included is a 22-page section entirely devoted to pigments, clearly explaining this confusing area to the less experienced artist. Straightforward sketching material such as pencil and charcoal to more challenging options of egg tempura and oils are included.